2021
DOI: 10.1038/s41597-021-00811-3
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive multimodal foetal ECG–Doppler dataset for antenatal cardiology research

Abstract: Non-invasive foetal electrocardiography (fECG) continues to be an open topic for research. The development of standard algorithms for the extraction of the fECG from the maternal electrophysiological interference is limited by the lack of publicly available reference datasets that could be used to benchmark different algorithms while providing a ground truth for foetal heart activity when an invasive scalp lead is unavailable. In this work, we present the Non-Invasive Multimodal Foetal ECG-Doppler Dataset for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…With regard to other work on the NInFEA dataset, Sulas et al[3] reported a correlation coefficient of 0.89 between their QRS detection algorithm and ultrasound for instantaneous fetal heart rate over all records. In the present work, for the 57 records successfully processed (excluding the last few seconds of a record that did not fall into a 5 s segment), the correlation coefficient for instantaneous heart rate/RR interval was 0.99.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to other work on the NInFEA dataset, Sulas et al[3] reported a correlation coefficient of 0.89 between their QRS detection algorithm and ultrasound for instantaneous fetal heart rate over all records. In the present work, for the 57 records successfully processed (excluding the last few seconds of a record that did not fall into a 5 s segment), the correlation coefficient for instantaneous heart rate/RR interval was 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, for the 57 records successfully processed (excluding the last few seconds of a record that did not fall into a 5 s segment), the correlation coefficient for instantaneous heart rate/RR interval was 0.99. Sulas et al[3] derived the ultrasound RR intervals through visual inspection whereas, in the present work, that process was performed by algorithm. Keenan et al[11] applied a prior fetal ECG extraction approach [12] to NInFEA to assess reliability of electrode/lead selection; results were reported in terms of a reliability measure based on a +/-10 beats/minute difference between ECG detected peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dataset. We consider the dataset from [54], which is publicly available 2 on PhysioNet [16]. This dataset was recently published and is part of an ongoing effort to establish a benchmark for noninvasive fECG extraction methods.…”
Section: Fetal Ecg Extractionmentioning
confidence: 99%
“…The obtained video was converted into a 1D time-series using a processing scheme based on envelope detection. The code for this processing scheme was provided as a Matlab-script by the authors of [54]. For convenience, we uploaded the obtained 1D time-series after applying the provided Matlab-script, and it is available at https: //github.com/ica-demos/ECG/tree/master/Data.…”
Section: C61 Datasetmentioning
confidence: 99%